ANALISIS KINERJA KEUANGAN PT ANEKA TAMBANG Tbk SEBELUM DAN SESUDAH AKUISISI - Ratnasari, Dita; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test whether there is a significant different on financial performance of PT Aneka Tambang Tbk before and after the acquisition. The financial performance is measured by using the nine financial ratios i.e.: current ratio, quick ratio, fixed assets turnover, total assets turnover, debt to asset ratio, debt to equity, net profit margin, return on assets and return on equity. This research is a case study research which focuses on PT Aneka Tambang Tbk which has conducted the acquisition in 2011. The financial statements which will be studied start from 2009 to 2013 periods. The paired samples t-test is used as the data analysis. The result of the research shows that the observation periods on the financial ratios 2 years before the acquisition and 2 years after the acquisition do not make any expected synergy since there is no significant different.Keywords: Acquisition, Financial Performance, Financial Performance.